Application of two-sample Mendelian randomization method to assess the causal relationship between rheumatoid arthritis and osteoporotic fracture - Zhenyu, Cai; Le, Chang; Shiyong, Zeng; Jinding, Lin; Mingzhong, Liu; Haifeng, Tang; Rongdong, Zeng (Frontiers in Medicine, 2024)
Background: The association between rheumatoid arthritis (RA) and osteoporotic fracture has garnered considerable attention; however, the causal relationships between diseases remain uncertain. Therefore, this study employed a Mendelian randomization (MR) analysis to investigate the causal effects of RA on osteoporotic fracture. Methods: The summary data for RA and osteoporotic fracture were extracted from the GWAS Catalog and Finn biobank database. The database provides information about diseased and health control subjects. We searched the database for the following conditions: RA, osteoporosis (OP) and osteoporotic fractures. Entries were published by investigating centers, which had established definitions and diagnostic criteria. We downloaded and processed the data to obtain the single-nucleotide polymorphisms (SNPs) strongly associated with RA, OP, and osteoporotic fracture. RA genetic associations were obtained from GWAS Catalog including 1961 cases and 454387 controls. The osteoporosis of GWAS Catalog involved 991 cases and 455357 controls, and the data of Finn biobank involved 8017 cases and 391037 controls. Genetic associations for osteoporotic fracture were taken from Finn biobank of 1822 cases and 311210 controls.Significantly associated and independent SNPs meeting the criteria of p < 5×10-8, r2 < 0.001, and kb = 10,000 were selected for MR analysis. The inverse variance weighted (IVW) method along with other MR methods was employed for analysis, while sensitivity analyses were conducted to assess reliability and stability.Results: The results provided strong evidence that RA was causally and positively associated with osteoporosis from the GWAS Catalog (OR = 1.16590; 95% CI: 1.04067 to 1.30619; P = 0.00811) and the Finn biobank database (OR = 1.07314; 95% CI: 1.03455 to 1.11317; P = 0.00016).Moreover, positive causal relationship was detected between RA and osteoporotic fracture (OR = 1.10132; 95% CI: 1.00506 to 1.20680; P = 0.03863). The results were robust according to sensitivity tests.Conclusions: This study showed positive causal relationships between RA and osteoporotic fracture. These results should be considered in further studies and public health measures on osteoporosis prevention strategies.